PENGEMBANGAN TiO2 PADA ABU DASAR BATUBARA (BOTTOM ASH) DAN UJI AKTIVITASNYA SEBAGAI FOTOKATALIS DALAM DEGRADASI ZAT WARNA METILEN BIRU - , TUTY ALAWIYAH,S.Si, Dr. Nurul Hidayat Aprilita, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Preparation and characterization of TiO2 immobilization on bottom ash (TiO2-bottom ash), and its activity test as a photocatalyst in degradation of methylene blue dyes have been conducted. The preparation was performed by adsorption using titanium (IV) isopropoxide as a source of Ti on bottom ash as a matrix, which followed by thermal treatment at 500 Â°C for 5 hours. The characterizations were performed using XRD, FTIR, and XRF methods to determine the effect impregnated of TiO2. The activity TiO2-bottom ash photocatalyst on photodegradation of methylene blue dyes was carried out by batch method in a closed reactor with UV lamp and stirring system. Th degradation result of methylene blue was measured using UV-Vis spectrophotometer at 650 nm. The influences of the Ti concentration immobilization on bottom ash, time of photodegradation, and mass of TiO2-bottom ash photocatalyst have also been studied. The result of the research show that the increase of Ti concentrations, can the increase of TiO2 content in TiO2-bottom ash with the same crystalinity. TiO2-bottom ash shows higher activity in the process of photodegradation than the pure TiO2, and bottom ash do. The longer irradiation time can increase the effectiveness of the photodegradation of methylene blue dye by TiO2-bottom ash photocatalyst up to 300 minutes with the degradation result of 88.25%, but for irradiation time longer than 300 minutes causes a decrease in the effectiveness of the photodegradation. The increase of TiO2-bottom ash photocatalyst mass up to 50 mg can improve the effectiveness of the photodegradation of methylene blue dye, but further increasing of mass result of the decrease in the photodegradation.